A Convenient Fluorescent Method to Simultaneously Determine the Enantiomeric Composition and Concentration of Functional Chiral Amines. Issue 50 (27th October 2014) - Huang, Zeng; Yu, Shanshan; Zhao, Xue; Wen, Kaili; Xu, Yimang; Yu, Xiaoqi; Xu, Yong; Pu, Lin
Abstract A 1, 1′‐bi‐2‐naphthol (BINOL)‐based chiral aldehyde in combination with ZnII shows a highly enantioselective fluorescent response toward functional chiral amines at λ>500 nm. However, the combination of salicylaldehyde and ZnII gives the same fluorescent enhancement for both enantiomers of a functional chiral amine at λ=447 nm. By using the fluorescent responses of the combination of the BINOL‐based chiral aldehyde, salicylaldehyde and ZnII at the two emission wavelengths, both the concentration and enantiomeric composition of functional chiral amines such as amino alcohols, diamines, and amino acids can be simultaneously determined by a single fluorescent measurement. This work provides a simple and convenient method for chiral assay.